2015
DOI: 10.7150/jca.10336
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: We Should Not Forget The Past

Abstract: Cancer has been in existence longer than human beings, and man has been facing the illness ever since he made his appearance on Earth. Amazingly, the first human cancer gene was cloned only thirty years ago. This, and other extraordinary scientific goals achieved by molecular cancer research in the last 30 years, seems to suggest that definitive answers and solutions to this severe disease have been finally found. This was not the case, as cancer still remains to be defeated. To do so, cancer must be first und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 54 publications
(96 reference statements)
0
18
0
4
Order By: Relevance
“…The concept of margin in oncologic surgery is almost six centuries younger than the word "cancer", which was coined by Hippocrates in view of the appearance of blood vessels surrounding a tumor and resembling the claws of a crab [3,4]. Thereafter, cancer was considered mostly as a "humoral disease", which was consequently deemed as non-curable through simple surgical excision.…”
Section: Historical Background: the Concept Of "Margin"mentioning
confidence: 99%
“…The concept of margin in oncologic surgery is almost six centuries younger than the word "cancer", which was coined by Hippocrates in view of the appearance of blood vessels surrounding a tumor and resembling the claws of a crab [3,4]. Thereafter, cancer was considered mostly as a "humoral disease", which was consequently deemed as non-curable through simple surgical excision.…”
Section: Historical Background: the Concept Of "Margin"mentioning
confidence: 99%
“…The association between inflammation and cancer is widely recognized. In 1863, Rudolf Virchow (3,4) reported that some tumors were infiltrated by inflammatory cells, leading to the hypothesis that inflammation is associated with cancer. In 2012, the International Agency for Research on Cancer established that infection with some pathogens, including Helicobacter pylori, human papillomavirus (VPH) variant 16, and Schistosoma haematobium, is associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancers can also arise in other organs with poor regenerative capacity due to faciliatory changes in tumorigenic- or tumor suppressor-pathways 27 . The possibility that they may also do so either by subverting dormant regenerative pathways in terminally differentiated cells or by inducing stem cell proliferation 12 , remains to be tested.…”
Section: Discussionmentioning
confidence: 99%